Effect of parental presence on fear and cooperation of 4-6 year-old children referring to Isfahan Faculty of Dentistry - Mahdi Jaafarzadeh; Alireza Eshgi; Fatemeh Farahbakhshpour; Sepideh Kazemizadeh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Fear and anxiety due to the dental treatment decrease cooperation of the child during the procedure. Since the majority of parents are willing to accompany their children in the operating room, the present study was carried out to evaluate the effect of parents' presence on fear and cooperation of children aged 4-6 years, referring to the Department of Pediatric Dentistry in Isfahan Faculty of Dentistry.Materials and Methods: This cross-sectional study was carried out on fifty systemically and mentally healthy 4-6 year-old children referring to Isfahan Faculty of Dentistry, with no previous dental experience. The subjects were randomly divided into two groups. In the first group, 25 subjects were accompanied by their parents during the whole procedure. In the second group, the subjects were not accompanied by anyone. During the treatment, the cooperation rate of each child was assessed by Franckle index and after the treatment, the fear score of each child was measured with the CFSS-DS questionnaire (child fear schedule survey - dental subscale). T-test and Mann-Whitney were used to compare dental fear and cooperation between the two groups, respectively. Spearman's correlation coefficient was used to assessing fear scores and cooperation rates (α = 0.05).Results: The means of fear scores in the presence and absence of parents were 26.60 ± 6.40 and 28.80 ± 10.61, respectively. There were no significant differences in fear rates and cooperation levels of children between the two groups based on CFSS-DS (p value = 0.37 and 0.79, respectively). There was a significant but inverse correlation between fear scores and cooperation levels (r = 0.783, p value < 0.001).Conclusion: Based on the results of the present study, parental presence or absence does not affect fear and cooperation of 4-6 year-old children during dental procedures. Key words: Child, Dental anxiety, Patient cooperation.